A systemic view of the aspects that constitute human motricity - Castaner, M.; Camerino, O. (International Journal of Computer Science in Sport, 2002)
Our aim is only to show some ideas, we consider to be very plain -but not simple-, that we have been observing, that paradoxically are blanks on the knowledge of many professionals on Physical Education and Sport.